NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis